Attention - Rensink, Ronald (Henry Stewart Talks, 2010)
How do we see scenes?, Older view of attention, Preattentive systems: psychological and behavioral studies, Orientation, Reaction time, Interpretation, What is processed preattentively?, Scene-based properties, Initial stages of visual processing, Identification of shadows, Completion of occlusion, Attentional systems, Change blindness, Attention is needed to perceive change in an object, Coherence theory, How much can we attend to?, Virtual representation, Triadic architecture, Nonattentional systems, Non-conscious detection of change, Newer view of attention
Reviewed at 2020/05/01